Parenting Styles on Childhood Injury Prevention: Insights from Nursing Mothers In Niger Delta Primary Health Care Settings (International Journal of Scientific Research in Science and Technology, 2025)
This study examined the effect of health education interventions on maternal knowledge, child injury prevention practices across varied style of parenting in urban and rural localities. An ex post facto research design was utilized involving 447 respondents as sample for the study selected from a population of 44,732 using a stratified random sampling technique. Data were collected using validated questionnaire and an observational checklist whose reliability, Cronbach’s alpha of r =0.86. Descriptive and inferential analyses of ANOVA and multiple regression, were used to test hypotheses at a 0.05 significance level. Results indicated a significant improvement in maternal knowledge mean scores of post-intervention (Mean = 78.4, SD = 5.62) compared to pre-intervention levels (Mean = 52.7, SD = 7.41; p < 0.001). Authoritative parents exhibited the highest adherence to safety practices (M = 81.2, SD = 4.89), while permissive and neglectful parenting styles revealed comparatively lower improvements (M = 64.3, SD = 6.75; M = 59.8, SD = 7.22). The study therefore recommends that integrating parenting skills training with socio-economic support into health education initiatives could enhance sustainability and effectiveness. These findings emphasized the need for tailored interventions that can optimize better outcomes for children in the region.
Keywords: Health education; child injury prevention; parenting styles; parental counseling; community-based interventions; child safety policies